Pemberdayaan Guru Dalam Implementasi Kurikulum 2013 di SD Negeri 1 Delanggu - Asmawulan, Tri, Prof. Dr. Yetty Sardjono, M.Si, Dr. Sabar Narimo, M.M., M.Pd (2014)
This study aims to: 1) Describe theteacher profile in public elementary school 1 Delanggu; 2) Describe the teacher empowerment in public elementary school 1 Delanggu; 3) Describe the implementation of Curriculum 2013 in public elementary school 1 Delanggu. This research is qualitative. Informants in this study were principals andteachers in primary school 1 Delanggu. Data was collected through interviews, observation and documentation. Data analysis techniques used in this research is the analysis of interactive models, namely data reduction, data display and conclusion. Remedy to test the credibility of the data using triangulation techniques. The results of this study: 1) Profile of teachers in primary schools 1 Delanggu good enough indicated by 80% of teacher education has met the qualifying standard. But in primary school 1 Delanggu not have teachers BK; 2) In terms of empowerment, there is a lack of professional competence that teachers do not do research, as well as the teacher's ability to operate a computer less. There is also a short age in teachers' personal competence are less disciplined time; 3) Implementation of Curriculum 2013 in primary school 1 Delanggu in planning have constraints on the availability of text books to support learning activities. While the implementation of primary school 1 Delanggu implement Curriculum 2013 is not in accordance with the time scheduled by the government. Even so, primay school 1 Delanggu been able to implement Curriculum 2013 in the learning process well. For the evaluation, because the first year of implementing the new curriculum in 2013, so it can not be evaluated as normative and summative